Upregulation of Transforming Growth Factor-β Expression in UVB-Irradiated BALB/c Mice Skin - Nuraniar Bariq Kinayoh; Aletheia Threskeia (Jurnal Biologi Tropis, 2026)
Chronic ultraviolet B (UVB) radiation induces progressive alterations in skin tissue that contribute to photoaging, while the involvement of Transforming growth factor-β (TGF-β) in this process remains unclear. This study aimed to analyze dermal TGF-β expression in the skin of BALB/c mice following chronic UVB irradiation. This true experimental study employed a post-test-only control group design, with 16 BALB/c mice divided into a normal control group (K1) and a UVB-exposed group (K2). Mice in group K2 were exposed to UVB at 1 minimal erythemal dose (MED; 240 mJ/cm²) six times per week for 27 days (24 exposures). Skin samples were collected immediately after the final exposure and analyzed using immunohistochemistry. Dermal TGF-β expression was significantly higher in the UVB-exposed group (17.70 ± 1.25) compared to the control group (11.08 ± 0.66) (p < 0.05). Chronic UVB exposure induces upregulation of dermal TGF-β expression, indicating altered regulation of this growth factor under prolonged inflammation. These findings provide preliminary evidence of altered TGF-β regulation under chronic UVB exposure and support further investigation into its role in photoaging.